PENGARUH KOMPETENSI GURU TERHADAP KINERJA GURU - Hendri Rohman (MADINASIKA, 2020)
The study was inspired by the phenomenon of the low performance of MTs teachers. which is reflected in the low ability to meet the standards set. Aims to analyze and find out: a) teacher competence; b) teacher performance; and c) the magnitude of the influence of teacher competence on MTs Sumedang District teachers. The research approach used is quantitative research with survey methods. Types of data consist of primary and secondary data, data collection tools using a questionnaire that is distributed to respondents who are taken proportionally. The data were processed using parametric statistics. Hypothesis testing using t-test and F-test. The results of data processing and analysis show that pedagogical competence, personality competence, social competence, and professional competence both partially and simultaneously have a significant effect on teacher performance with an influence of 00%. In conclusion, teacher competence with its four dimensions has a significant effect on MTs teacher performance.